2004
DOI: 10.1590/s1678-58782004000300005
|View full text |Cite
|
Sign up to set email alerts
|

Normal force calculations for rocket-like configurations

Abstract: Transonic and supersonic flow simulations over typical launch vehicle configurations are presented. A 3-D finite difference numerical code, written for general, curvilinear, body-conforming coordinate systems, is used. The code solves the thin-layer approximation for the laminar Navier-Stokes equations. Simulations are performed for a launcher and a sounding rocket configurations, currently under development at Instituto de Aeronáutica e Espaço. Calculations consider cases at angle of attack and at various fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…4). The Reynolds number based on the airfoil chord and the midvalue of interval (5) is 5:4 Â 10 6 . In order to assess the numerical accuracy of the solution, we tested three different meshes by varying both the number of grid nodes and the grid clustering.…”
Section: Formulation Of the Problem And A Numerical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4). The Reynolds number based on the airfoil chord and the midvalue of interval (5) is 5:4 Â 10 6 . In order to assess the numerical accuracy of the solution, we tested three different meshes by varying both the number of grid nodes and the grid clustering.…”
Section: Formulation Of the Problem And A Numerical Methodsmentioning
confidence: 99%
“…The small local curvature is attributed also to surfaces of engine nacelles [4], compressor blades [5], and enlarged diameter bays of missiles [6,7]. At the same time, physical phenomena associated with transonic flow over flattened surfaces have not been well understood.…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing existing records of flying squid events, the squid launches out of water in a short time. To reduce pitch moment induced by lateral loads (especially when moving underwater), the body longitudinal axis and velocity vector of a launching vehicle are consistent during each launching phase [44,45]. The same principle applies to the squid motion as well.…”
Section: Launch Angles and Assumptionsmentioning
confidence: 99%
“…Fig. 8 is normal force distribution along body-axis (x-direction) 16 (or, sectional line-load 12 ). This is obtained only from simulation, and shows that Nose Faring and SMSJ give local peaks (it is confirmed that SMSJs play a major role).…”
Section: B Normal Force and Pitching Moment: Case A5_phi00_epsilonrewtmentioning
confidence: 99%
“…Similar studies for other rocket configurations were conducted in Refs. [8][9][10][11][12][13][14][15][16], but our work differs from them in the following aspects. Firstly, those studies [8][9][10][11][12][13][14][15][16] presented either of aerodynamic characteristics, flow simulations, or wind-tunnel experiments independently; however, our study shows all those results and relates them together to thoroughly understand detailed flow structure and aerodynamics of the rocket.…”
Section: Introductionmentioning
confidence: 96%